Improving the Poetry Writing Skills of Year 10 Culinary Students Through the Imaginative Suggestion Method at SMKN 1 Bojonegoro - Elviana Diah Rosmita; Heny Subandiyah (Transpublika Publisher, 2026)
The skills of writing poetry is one of the basic competencies of Indonesian language taught in vocational schools. Based on observations and interviews conducted during the SFI at SMKN 1 Bojonegoro, students have difficulty writing poetry in terms of structural aspects, due to the use of methods and media that are less engaging, which leads to limitations in ideas and imagination. As a result, the average student score remains below the MPM of 75. This study aims to: (1) describe the application of the suggestion-imagination method, (2) examine the improvement of poetry writing skills, and (3) analyze student responses toward poetry writing learning, all conducted in Class X-Culinary 1 at SMKN 1 Bojonegoro through the suggestion-imagination method using song video clips by Moch. Arifin. This study uses the design of Kemmis and Mc. Taggart CAR models in two cycles with the subject of students X-Culinary 1 SMKN 1 Bojonegoro. The data collected consists of the activities of teacher and students, the value of poetry writing skills, and responses of students. The results showed that the activity of teacher increased from cycle I (75) to Cycle II (89), while students increased from cycle I (74) to Cycle II (88). The value of students increased from cycle I (72.84) to Cycle II (83.20) with a percentage of 80% completeness. Students give a positive response 90% with the category of strongly agree. This study concluded that the method of imagination suggestion with video clips of songs can improve students ' poetry writing skills.